Bioethanol Steam Reforming over Cobalt-Containing USY and ZSM-5 Commercial Zeolite Catalysts - Grzybek, Gabriela; Greluk, Magdalena; Tarach, Karolina; Pyra, Kamila; Słowik, Grzegorz; Rotko, Marek; Góra-Marek, Kinga (Frontiers in Materials, 2020)
The ethanol steam reforming process (ESR) over cobalt-based zeolitic catalysts, differing significantly in the structure, was comprehensively examined. The cobalt spinel phase (10wt%) was deposited on the surface of USY and ZSM-5 zeolites (Si/Al ratio of 31). The catalysts were characterized in terms of their chemical (ICP) and phase composition (XRD), textural properties (low-temperature N2 adsorption), morphology (STEM/EDX), and reducibility (H2-TPR). The aforementioned characteristics were supplemented by the catalysts’ acidity and redox properties investigations (quantitative FT-IR studies of pyridine and carbon monoxide adsorption). Catalysts' activity was evaluated in the ESR process at 500C for various ethanol/water mixtures. Both catalysts exhibited 100% ethanol conversion, whereas their selectivity towards H2, CO2, and C2H4 strongly depended on the applied ethanol to water molar ratio. Comparable selectivities observed for the 1:4 ratio were improved for the 1:9 ratio for both catalysts, as expected. For the ratio of 1:12, the significant difference in the reaction paths (the ethanol dehydration for CoUSY and the ethanol steam reforming for CoZSM-5) was explained by the cobalt reoxidation process facilitated by water molecules for the CoUSY. The superior overall performance of the CoZSM-5 catalyst in the ESR process, in comparison to CoUSY, also results from its almost three times enhanced accessibility of the cobalt species, as confirmed by the quantitative FT-IR studies of CO sorption. The microscopic studies also indicated a better dispersion of the cobalt phase supported on the ZSM-5 support. Thus, the structure of ZSM-5 zeolite assures higher cobalt active phase dispersion being more beneficial for the ESR process.